Teachers’ Attitudes Toward Government-Mandated Provincial Testing in Manitoba - Skwarchuk, Sheri-Lynn (Alberta Journal of Educational Research, 2003)
Government-imposed testing has been introduced in Canada to establish benchmarks, improve accountability, and measure achievement consistently. In this study 133 teachers from urban and rural Manitoba completed surveys (a response rate of 34%) to ascertain their attitudes toward mandated testing. Results indicated that most teachers expressed negativity about exam use, but attitudinal differences were contingent on location and teacher involvement in implementation. Teachers reported using many preparation strategies, but only developing study skills correlated positively with grade 3 exam scores. The findings are discussed in terms of the efficacy of using mandated exams and identifying appropriate preparation strategies.